Clinical, molecular and histopathological features of short stature syndrome with novel CUL7 mutation in Yakuts: new population isolate in Asia. Issue 12 (3rd August 2007) - Maksimova, N; Hara, K; Miyashia, A; Nikolaeva, I; Shiga, A; Nogovicina, A; Sukhomyasova, A; Argunov, V; Shvedova, A; Ikeuchi, T; Nishizawa, M; Kuwano, R; et al.
Abstract : Background: In total, 43 patients having short stature syndrome in 37 Yakut families with autosomal recessive prenatal and postnatal nonprogressive growth failure and facial dysmorphism but with normal intelligence have been identified. Methods: Because Yakuts are considered as a population isolate and the disease is rare in other populations, genomewide homozygosity mapping was performed using 763 microsatellite markers and candidate gene approach in the critical region to identify the causative gene for the short stature syndrome in Yakut. Results: All families shared an identical haplotype in the same region as the identical loci responsible for 3-M and gloomy face syndromes and a novel homozygous 4582insT mutation in Cullin 7 ( CUL7 ) was found, which resulted in a frameshift mutation and the formation of a subsequent premature stop codon at 1553 (Q1553X). Yakut patients with short stature syndrome have unique features such as a high frequency of neonatal respiratory distress and few bone abnormalities, whereas the clinical features of the other Yakut patients were similar to those of 3-M syndrome. Furthermore, abnormal vascularisation was present in the fetal placenta and an abnormal development of cartilage tissue in the bronchus of a fetus with CUL7 mutation. Conclusion: These findings may provide a new understanding of the clinical diversity and pathogenesis of short stature syndrome with CUL7 mutation.